Effect of hot drying on the essential oil content and colour charactiristics of peppermint (Mentha piperita) - Chi, Nguyen Thi Kim; Thanh Thao, Duong Thi; Tuan, Hoang Quoc (Vietnam Journal of Science and Technology, 2016)
The main objective of this study was to investigate the effect of different temperature of hot air drying on the qualities of dried peppermint included essential oil content, colour parameters, colour sensory quality and modelling the colour change kinetics. The drying experiments were carried out at five air temperature of 40, 50, 60, 70 and 80oC. The colour parameters for colour change of the materials were quantified by the Hunter L (whiteness/darkness), a (redness/greenness) and b (yellowness/blueness) system. These values were also used for calculation of total change (DE) as well as chroma, hue angle and Browning index. A consumer preference test was conducted with 80 consumers to assess the colour quality of 05 dried peppermints. The results showed that the decreasing of essential oils content at high drying temperature is higher than at low temperature. Least Squares regression was used to determine the relationship between colour sensory scores of consumer taster and quantification of three Hunter parameters. In that, variable “L” and “b” could be distributed to decreasing while variable “a” contributory increase the colour quality of dried peppermint products. It was observed that L, a, DE and hue angle values were fitted to the zero-order model, while b and chroma were fitted to the first-order model.